PPE or not PPE - that is the question - D’Cruz, Len (Br Dent J, 2020)
The world is in the middle of the COVID-19 pandemic and healthcare workers as well as dentists are having to make every difficult decision about their responsibilities in caring for their patients. Compounding this is the shortage of personal protective equipment (PPE), which makes patient-centred care ethically more challenging. Our first response to these ethical challenges should be to start with ourselves to make sure we are safe before we think about the patients. This is not the approach we would normally adopt when treating our patients outside of a pandemic.